2013
DOI: 10.1557/opl.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Analysis of Glasses in the Al2O3-B2O3-Fe2O3-Na2O-SiO2 System

Abstract: Glasses in the Al 2 O 3 -B 2 O 3 -Fe 2 O 3 -Na 2 O-SiO 2 system were produced at a temperature of 1150 °C, annealed, and examined using XRD and SEM/EDX. Surfaces of same samples were additionally heattreated and etched with HCl. The pristine samples were X-ray amorphous and rather homogeneous except the B1 sample that contained trace crystalline phases of carnegieite/nepheline and spinel. Corrosion of these glasses via an etching treatment proceeds by a conventional mechanism with damage of their surface layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As follows from theoretical suggestions (see our previous paper [7]), the majority of boron in these glasses must be four-coordinated on oxygen. As follows from theoretical suggestions (see our previous paper [7]), the majority of boron in these glasses must be four-coordinated on oxygen.…”
Section: Infrared Spectramentioning
confidence: 58%
“…As follows from theoretical suggestions (see our previous paper [7]), the majority of boron in these glasses must be four-coordinated on oxygen. As follows from theoretical suggestions (see our previous paper [7]), the majority of boron in these glasses must be four-coordinated on oxygen.…”
Section: Infrared Spectramentioning
confidence: 58%
“…XRD and SEM characterization showed that the A1 and D1 materials were fully amorphous whereas the B1 material contained a minor content of carnegieite crystals (Na1.13Al0.75Fe0.22Si0.99O4.00) and a very low concentration of magnetite-type spinel crystals [18,19]. Due to the low content of these phases in the B1 glass their effect on Fe partitioning is negligible and the majority of Fe in the glass enters the vitreous phase similar to the A1 and D1 glasses.…”
Section: Discussionmentioning
confidence: 99%
“…The target and measured chemical compositions of the glasses are given in Table I. The glasses were characterized by X-ray diffraction, electron microscopy, infra-red (IR) and Raman spectroscopy in our previous studies [18,19]. X-ray absorption fine structure (XAFS) spectra were recorded at the Structural Materials Science (STM) beamline of the synchrotron source at NRC "Kurchatov Institute" [20].…”
Section: Methodsmentioning
confidence: 99%